The Development of Context-Sensitive Attention Across Cultures: The Impact of Stimulus Familiarity - Jurkat, Solveig; Köster, Moritz; Yovsi, Relindis; Kärtner, Joscha (Frontiers in Psychology, 2020)
Across cultures, there are marked differences in visual attention that gradually develop between 4 to 6 years of age. According to the social orientation hypothesis, people in interdependent cultures should show more pronounced context sensitivity than people in independent cultures. However, according to the differential familiarity hypothesis, the focus on the salient object should also depend on the familiarity of the stimulus; people will focus more on the focal object (i.e., less context sensitivity), if it is a less familiar stimulus. To examine the differences in visual attention between interdependent and independent cultures while taking into account stimulus familiarity, this study used an eye-tracking paradigm to assess visual attention of participants between 4 and 20 years who came from urban middle-class families from Germany (n = 53; independent culture) or from Nso families in a rural area in Cameroon (n = 50; interdependent culture). Each participant saw four sets of stimuli, which varied in terms of their familiarity: (1) standard stimuli and (2) non-semantic stimuli, both more familiar to participants from Germany, as well as (3) culture-specific matched stimuli and (4) simple stimuli, similarly familiar to the individuals of both cultures. Overall, the findings show that mean differences in visual attention between cultures were highly contingent on the stimuli sets: In support of the social orientation hypothesis, German participants showed a higher object focus for the culture-specific matched stimuli, while there were no cultural differences for the simple set. In support of the differential familiarity hypothesis, the Cameroonian participants showed a higher object focus for the less familiar sets, namely the standard and the non-semantic set. Furthermore, context sensitivity correlated across all the sets. In sum, these findings suggest that the familiarity of a stimulus strongly affects individuals’ visual attention, meaning that stimulus familiarity needs to be considered when investigating culture-specific differences in attentional styles.